Transferability between soil organic matter measurement methods for database harmonization - Shamrikova, E.V.; Kondratenok, B.M.; Tumanova, E.A.; Vanchikova, E.V.; Lapteva, E.M.; Zonova, T.V.; Lu-Lyan-Min, E.I.; Davydova, A.P.; Libohova, Z.; Suvannang, N. (Geoderma, 2022)
•Soil Organic Carbon was analyzed by Tyurin, Walkley-Black and Dry Combustion methods.•Tyurin oxidized slightly more SOC (83%) than Walkley-Black (77%).•Dry Combustion oxidized more C than Tyurin and Walkley-Black, but not significantly.•Conversion factor from Corg by DC were 1.15 and 1.3 for Walkley-Black and Tyurin.•The Conversion factor varied from 0.9 to 1.5 and slightly decreased with SOM increase. Soil organic matter (SOM) is one of the most important soil-forming factors and complex with a chemical composition not fully known. The amount of SOM traditionally is estimated by stoichiometric determination of carbon dioxide (CO2) released from oxidation reaction with a chromium mixture, hence the term soil organic carbon (SOC). The two most common oxidation methods are Tyurin (T) and Walkley-Black (WB). However, the efficiency of organic carbon oxidation depends upon the conditions of the oxidation reduction (redox) reaction (temperature, reagent concentration, oxidation time), which vary for both methods. The lack of consistent results from the oxidation methods has led to widely different conversion factors. Although the Tyurin’s method has been slowly removed from some laboratories, there still remains a large number of samples, especially from Eurasia, that have been measured by this method for more than a century and continue at the present time. The objective of this research was to develop equations or pedotransfer functions (ptf) for converting SOC determined by the Tyurin method to current and more widely used methods, such as WB and dry combustion (DC). A comparative analysis was performed for the assessment of soil organic carbon content obtained by Tyurin and Walkley-Black methods for ten quality control soil samples and 100 field soil samples. The selected soils differed in their genesis, geographical origin, and organic carbon content. SOC determined by dry combustion, providing a maximum oxidation of organic carbon, was used as a standard for comparing Tyurin and WB methods. The conversion factors from Corg by DC developed from equations (ptf) were 1.15 and 1.30 for WB and Tyurin methods. The SOM measurement error for both methods did not exceed 20%. The relationship between the absorption of calibration solutions and the mass of sucrose carbon or the equivalent amount of iron (II) for the entire OC range in this study was very strong (r = 0.99). The values of the calibration function coefficients (A0, K) of the calibration functions A = A0 + Km (OC) for both methods, did not depend upon the nature of the reducing agent. The relative error of the K coefficients when using two reducing agents (Mohr’s salt or sucrose) was not more than δ2 ≤ 2.5%. Soil samples prepared using the Tyurin method experienced additional dispersion compared to the Walkley-Black method, which caused higher values in the measurement of SOC even after centrifugation of soil suspensions. The mean SOC measured value by the Tyurin method combined with 48 h settling time was comparable with the mean SOC measured by dry combustion. The established coefficients ensure that the results are transferable and consistent with the standard method. The results from this study facilitate the integration of the accumulated data that are analyzed by different methods across the Eurasian countries into one comprehensive database that could be incorporated into the global network for monitoring soil quality and carbon stocks